Proyección para la adecuación del aula a-113 para instalar equipos de procesamientos de alimentos en la Universidad Antonio Nariño sede Cartagena (2020)
The projection project for the adaptation of Classroom A-113 to install food processing, aims to establish the procedure to be performed for the construction and improvement required in classroom A-113 complying with the standards established by the ministry of health under Law 09 of 1979 of Decree 3075 for the fulfillment of a safe and free workplace of contaminant, where the handling will be carried out of food within the Antonio Nariño University Cartagena headquarters. Once the information required to the adaptation of the classroom A113. The projection was made of the resource required for the adaptation of the classroom A- 113 establishing the necessary budget for your implementation and achieve classroom improvement to meet with the need to promote the development of production and handling of food within the installation of the Antonio Nariño University headquarters Cartagena.